2005
DOI: 10.1128/aem.71.2.987-992.2005
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan Acanthamoeba polyphaga as a Potential Reservoir for Campylobacter jejuni

Abstract: We showed by a laboratory experiment that four different Campylobacter jejuni strains are able to infect the protozoan Acanthamoeba polyphaga. C. jejuni cells survived for longer periods when cocultured with amoebae than when grown in culture alone. The infecting C. jejuni cells aggregated in amoebic vacuoles, in which they were seen to be actively moving. Furthermore, a resuscitation of bacterial cultures that were previously negative in culturability tests was observed after reinoculation into fresh amoeba c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
132
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(149 citation statements)
references
References 22 publications
11
132
3
3
Order By: Relevance
“…Acanthamoeba spp., as an opportunistic pathogen, are among the major colonizing pathogen for granulomatous amoebic encephalitis (GAE) and a common infectious agent in amoebic keratitis (AK) and immunocompromised hosts such as AIDS patients (Siddiqui and Khan 2012;Trabelsi et al 2012). Acanthamoeba is a Trojan horse for microorganisms such as Escherichia coli O157, Legionella pneumophila, Coxiella burnetii, Helicobacter pylori, Chlamydophila pneumoniae, Vibrio cholerae, Listeria monocytogenes, Campylobacter jejuni, Mycobacterium leprae and Pseudomonas aeruginosa (Axelsson-Olsson et al 2005;Greub and Raoult 2004;Winiecka-Krusnell and Linder 2001). Prevalence of Acanthamoeba is correlated with the amount of organic matter present in the water, and its frequency is high in sediments and biofilms, which constitute ecological niches where they can feed on bacteria (Loret and Greub 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Acanthamoeba spp., as an opportunistic pathogen, are among the major colonizing pathogen for granulomatous amoebic encephalitis (GAE) and a common infectious agent in amoebic keratitis (AK) and immunocompromised hosts such as AIDS patients (Siddiqui and Khan 2012;Trabelsi et al 2012). Acanthamoeba is a Trojan horse for microorganisms such as Escherichia coli O157, Legionella pneumophila, Coxiella burnetii, Helicobacter pylori, Chlamydophila pneumoniae, Vibrio cholerae, Listeria monocytogenes, Campylobacter jejuni, Mycobacterium leprae and Pseudomonas aeruginosa (Axelsson-Olsson et al 2005;Greub and Raoult 2004;Winiecka-Krusnell and Linder 2001). Prevalence of Acanthamoeba is correlated with the amount of organic matter present in the water, and its frequency is high in sediments and biofilms, which constitute ecological niches where they can feed on bacteria (Loret and Greub 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some bacteria, however, are able to resist protozoan grazing, and can survive inside FLP cells. These include various foodborne pathogens such as Campylobacter jejuni (Axelsson-Olsson et al, 2005;Baré et al, 2010), Escherichia coli O157:H7 (Barker et al, 1999), Listeria monocytogenes (Zhou et al, 2007), Salmonella spp. (Gaze et al, 2003;Tezcan-Merdol et al, 2004), Staphylococcus aureus (Huws et al, 2008), Arcobacter butzleri (Medina et al, 2014) and Yersinia enterocolitica (Lambrecht et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…in drinking water supplies. However, laboratory based studies have demonstrated C. jejuni growth at ambient temperatures within amoebae [7,8], opening up the possibility for naturally occurring amoebae to prolong the persistence or even growth of C. jejuni within drinking water systems.…”
Section: Future Microbiologymentioning
confidence: 99%